Decoding of methylated histone H3 tail by the Pygo-BCL9 Wnt signaling complex. - Fiedler, M.; Sánchez-Barrena, M.J.; Nekrasov, M.; Mieszczanek, J.; Rybin, V.; Müller, J.; Evans, P.; Bienz, M. (Molecular Cell, 2008)
Pygo and BCL9/Legless transduce the Wnt signal by promoting the transcriptional activity of beta-catenin/Armadillo in normal and malignant cells. We show that human and Drosophila Pygo PHD fingers associate with their cognate HD1 domains from BCL9/Legless to bind specifically to the histone H3 tail methylated at lysine 4 (H3K4me). The crystal structures of ternary complexes between PHD, HD1, and two different H3K4me peptides reveal a unique mode of histone tail recognition: efficient histone binding requires HD1 association, and the PHD-HD1 complex binds preferentially to H3K4me2 while displaying insensitivity to methylation of H3R2. Therefore, this is a prime example of histone tail binding by a PHD finger (of Pygo) being modulated by a cofactor (BCL9/Legless). Rescue experiments in Drosophila indicate that Wnt signaling outputs depend on histone decoding. The specificity of this process provided by the Pygo-BCL9/Legless complex suggests that this complex facilitates an early step in the transition from gene silence to Wnt-induced transcription.